Mechanisms underlying immunosuppression by regulatory cells - Goldmann, Oliver; Nwofor, Obiageli Vivian; Chen, Qian; Medina, Eva (Frontiers in Immunology, 2024)
Regulatory cells, such as regulatory T cells (Treg), regulatory B cells (Breg) and myeloid-derived suppressor cells (MDSC) play a crucial role in preserving immune tolerance and controlling immune responses during infections to prevent excessive immune activation. However, pathogens have developed strategies to hijack these regulatory cells to decrease the overall effectiveness of the immune response and persist within the host. Consequently, therapeutic targeting of these immunosuppressive mechanisms during infection can reinvigorate the immune response and improve the infection outcome. The suppressive mechanisms of regulatory cells are not only numerous but also redundant, reflecting the complexity of the regulatory network in modulating the immune responses. The context of the immune response, such as the type of pathogen or tissue involved, further influences the regulatory mechanisms involved. Examples of these immunosuppressive mechanisms include the production of inhibitory cytokines such as IL-10 and TGF-b that inhibit the production of proinflammatory cytokines and dampen the activation and proliferation of effector T cells. In addition, regulatory cells utilize inhibitory receptors like cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) to engage with their respective on effector cells, thereby suppressing their function. An alternative approach involves the modulation of metabolic reprogramming in effector immune cells to limit their activation and proliferation. In this review, we will provide an overview of the major mechanisms mediating the immunosuppressive effect of the different regulatory cell subsets in the context of infection.